Chalk, Cheese, and Cloth: The Settling of Quaker Communities in Seventeenth-Century Wiltshire - Taylor, Kay S. (Quaker studies, 2006)
The underlying geology of Wiltshire was responsible for the county's contrasting farming and settlement patterns of the seventeenth century, and gave rise to its distinctive north-south 'chalk and cheese' divide. These particular characteristics, which also shaped the road networks and the location of the cloth-producing industry, played a significant role in determining the way in which the early Quaker movement developed within the county. This paper not only places the development of Wiltshire Quakerism within the context of the county's topography but also identifies the influence of other factors, such as patronage and the presence of other religious groups, on the settling of the network of Quakers' Meetings.